Social Resilience Among The Rubble : How Communities Construct New Identities After Disasters - Asror, Ahidul; Rosyid, Achmad Fathor (Socious Journal, 2025)
Disasters disrupt not only physical infrastructure but also social relations, collective identities, and community meaning systems. While disaster studies have extensively examined risk management, emergency response, and physical recovery, the social processes through which communities reconstruct identity and meaning in post-disaster contexts remain underexplored. This study examines social resilience as an interpretative and identity-based process through which communities actively reconstruct their social worlds after disasters. Using a qualitative sociological–interpretative approach, the research draws on in-depth interviews, participant observation, and analysis of community narratives involving disaster-affected communities. The findings demonstrate that social resilience is not a static capacity but a negotiated process shaped through collective narratives, solidarity practices, and symbolic actions. Communities redefine “who we are” by transforming experiences of loss into shared meanings that strengthen social bonds and collective agency. Furthermore, the construction of post-disaster identity occurs within unequal power relations, where community narratives often contest external representations imposed by state actors, humanitarian organizations, and media. In this sense, social resilience functions not only as adaptation but also as symbolic resistance against passive victimhood labels. The study contributes to disaster resilience scholarship by reframing resilience as a dynamic process of identity construction and meaning-making, offering a deeper understanding of post-disaster recovery beyond technical and material dimensions.